2011
DOI: 10.1097/dbp.0b013e318227b3dc
|View full text |Cite
|
Sign up to set email alerts
|

The Cues and Care Randomized Controlled Trial of a Neonatal Intensive Care Unit Intervention: Effects on Maternal Psychological Distress and Mother-Infant Interaction

Abstract: Nonspecific attention was as effective as an early skill-based intervention in reducing maternal anxiety and enhancing sensitive behavior in mothers of VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(156 citation statements)
references
References 54 publications
1
128
0
1
Order By: Relevance
“…were unable to demonstrate any significant changes in parent or infant outcomes [22]. A recent study of a skill-based program called “cues” was also unable to demonstrate any additional benefit over non-specific education [23]. However, in a randomised controlled trial, Melnyk et al , demonstrated that the COPE program, which focuses on providing parents with a very structured educational-behavioural program, improves parent coping and mental health outcomes during and after hospitalization, as well as shortening infants’ length of stay [6].…”
Section: Discussionmentioning
confidence: 99%
“…were unable to demonstrate any significant changes in parent or infant outcomes [22]. A recent study of a skill-based program called “cues” was also unable to demonstrate any additional benefit over non-specific education [23]. However, in a randomised controlled trial, Melnyk et al , demonstrated that the COPE program, which focuses on providing parents with a very structured educational-behavioural program, improves parent coping and mental health outcomes during and after hospitalization, as well as shortening infants’ length of stay [6].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the trials reported beneficial short and long-term infant and parent outcomes, including shorter hospital stay [55], better cognitive development [48,54,58,61], improved mother-infant interaction and attachment [49,56], reduced parenting stress [54][55][56], less maternal depression and anxiety [55,58], improved maternal confidence in parenting [55,58], better maternal sensitivity/ responsiveness [60], and higher maternal self-efficacy [61]. Two studies of a parent education program failed to find any effect on infant development, maternal stress/anxiety, or maternal-infant interaction [51,63]. However, the emphasis in these family-centred care programs has been to increase parent knowledge and confidence, but not to fully engage parents in all aspects of their infant's care.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Over the past 25 years several family-centred care programs have been developed and subjected to randomized controlled trials [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. These programs use one or more approaches, such as parent education, provision of psychological support, teaching developmental care, and facilitating better communication, to address a variety of domains including parent-infant interaction, parental knowledge and confidence, and parental stress.…”
Section: Previous Studiesmentioning
confidence: 99%
“…El 55 % de los estudios proporcionaron los tres componentes educativos de la intervención (44,45,47,50,52); el 33 % utilizó solo la información (42, 46, 51) y el 22 % no proporcionó apoyo emocional parental (42,46). Los nueve estudios incluidos informaron resultados paternos de estrés.…”
Section: Componentes De La Intervenciónunclassified